Effects of Ozone Fumigation on the Main Postharvest Pathogenic Fungi Penicillium sp. and the Storage Quality of Blueberry in Majiang County, China - Wu, Wenneng; Cao, Sen; Chen, Haijiang; Ruan, Lixiu; Lei, Qiqing; Xu, Su; Li, Jiangkuo (Frontiers in Plant Science, 2022)
In this study, the fungus Penicillium sp. was isolated from rotting postharvest blueberry fruits at different storage stage and identified to genera. Inoculation of this strain on the surface of fresh fruits was able to cause rotting. The strain was then used as a reference strain to test the chemical control effect of ozone fumigation during storage. The results showed that ozone fumigation had an obvious inhibitory effect on Penicillium sp. in a dose- and time-dependent manner. Meanwhile, ozone fumigation treatment could prevent the loss of fruit firmness, slow down the decrease of soluble solids, total phenolics and anthocyanins, and maintain lower activity of PPO and higher activities of POD and CAT. As far as we know, this is the first report on the effects of ozone fumigation on the postharvest pathogenic fungi Penicillium sp. and on the storage quality of postharvest blueberry collected from Majiang county, Guizhou province, China.